(untitled) (LIS TODAY, 2025)
The use of Information and Communication Technology or ICT is important in reforming or modernizing medical education and the healthcare system. The present study investigates the use of ICT tools by students, faculty and researchers at Indira Gandhi Institute of Medical Sciences (IGIMS), Patna. A total of 80 people were surveyed through a structured questionnaire, of which 65 valid responses were used for the analysis. It aimed to measure ICT use, frequency of use, awareness, and specific usage in the academic-clinical setting. The Results show a high percentage of use of ICT for academic learning, research, references for clinical practice and online resources. Nonetheless, the paper reveals that there is also little familiarity with more sophisticated ICT tools from an awareness perspective, lack of experience with user education workshops, and infrastructural and accessibility issues. But, in spite of these challenges there was significant receptivity towards the use of institutional repositories, medical databases, and ICT-based education among respondents. The findings provided perspectives on ICT’s increasing role in medical education and the need for digital skills to be dynamic. It also suggests better ICT training on a regular basis, a better infrastructure for ICT and awareness raising in order to make optimal use of online resources. This must be done to better use ICT in IGIMS, Patna for academic and clinical learning.